A SPATIAL STUDY OF LAND AND FOREST FIRE-PRONE AREAS IN SITUBONDO REGENCY, EAST JAVA PROVINCE - Putra, Haeropan Daniko; Manessa, Masita Dwi Mandini; Rokhmatulloh, Rokhmatulloh; Efriana, Anisya Feby; Haidar, Muhammad (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 17 No 1 (2023)DO - 10.24843/EJES.2023.v17.i01.p01, 2023)
The increasing area of land burned in 2021 makes the government urgent to map areas prone to forest fires in Situbondo Regency. This study analyzes areas prone to forest and land fires using the SMCA method. The research analysis used variables of land cover type, the greenness of vegetation, vegetation humidity, land surface temperature, and human factors. The human elements in question are accessibility (distance from the road network) and distance from human activities (distance from settlements, fields, and plantations). The conclusion analysis of forest fire-prone areas is divided into three classes that are high, medium, and low. From the vulnerability model that has emerged, it was found that most of Situbondo Regency have a high grade of forest fire vulnerability with an area of 652.66 km² (39.08%). The areas with the level of vulnerability of the middle, low, and non-vulnerable classes, respectively, are 532.12 km² (31.87%), 306.46 km² (18.35%), and 178.65 km² (10, 70%). The results of statistical tests using the ordinal logistic regression method show that natural factors for forest and land fires had a higher level of influence (? = 4.824) on forest and land fire vulnerability compared to human factors (? = 1.051). Keywords:  Forest and Land Fires; GMA method; Natural Factors; Human Factor